Higher versus lower positive end-expiratory pressure in patients without acute respiratory distress syndrome: a meta-analysis of randomized controlled trials - Pettenuzzo, Tommaso (Crit Care, 2021)
BACKGROUND: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the association of higher positive end-expiratory pressure (PEEP), as opposed to lower PEEP, with hospital mortality in adult intensive care unit (ICU) patients undergoing invasive mechanical ventilation for reasons other than acute respiratory distress syndrome (ARDS). METHODS: We performed an electronic search of MEDLINE, EMBASE, Scopus, Cochrane Central Register of Controlled Trials, CINAHL, and Web of Science from inception until June 16, 2021 with no language restrictions. In addition, a research-in-progress database and grey literature were searched. RESULTS: We identified 22 RCTs (2225 patients) comparing higher PEEP (1007 patients) with lower PEEP (991 patients). No statistically significant association between higher PEEP and hospital mortality was observed (risk ratio 1.02, 95% confidence interval 0.89–1.16; I(2) = 0%, p = 0.62; low certainty of evidence). Among secondary outcomes, higher PEEP was associated with better oxygenation, higher respiratory system compliance, and lower risk of hypoxemia and ARDS occurrence. Furthermore, barotrauma, hypotension, duration of ventilation, lengths of stay, and ICU mortality were similar between the two groups. CONCLUSIONS: In our meta-analysis of RCTs, higher PEEP, compared with lower PEEP, was not associated with mortality in patients without ARDS receiving invasive mechanical ventilation. Further large high-quality RCTs are required to confirm these findings. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13054-021-03669-4.